The Eﬃciency of a Head’s of a Forensic Organization Activity: Assessment Criteria, Conditions for Achieving and Correlation with the Goals of Forensic Activity - O. A. Surovaya (Теория и практика судебной экспертизы, 2021)
The article addresses the issues of the eﬃciency of forensic activity and its impact on the successful performance of forensic conduct. The author oﬀers a systematic analysis of the processes of forming eﬃciency indicators for forensic activity and assessment criteria for a Head’s of a forensic organization activity. The paper also describes qualitative and quantitative indicators of the eﬃciency of a forensic organization when assessing the eﬃcacy of a head’s performance, including by the eﬃciency indicators approved by the Ministry of Justice of the Russian Federation for forensic institutions of the system of the Ministry of Justice of the Russian Federation. The author analyzes the probabilities of the negative eﬃciency of a head’s activity and its impact on expert conduct. The article determines the trends of the further research of the issues of improving the eﬃcacy of forensic organizations’ activities by forming new criteria for assessing a forensic organization head’s performance inﬂuencing the quality of forensic conduct.